Perancangan Basis Data Multimedia Berbasis Cloud: Analisis Latensi dan Efisiensi Biaya - Fajar Fajar; Sesra Budio (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to analyze the design of a cloud-based multimedia database, focusing on access latency and cost efficiency in multimedia data management. With the increasing use of digital data particularly images, audio, and video there is a need for a storage system capable of providing large capacity, fast access, and more efficient operational costs. Cloud computing technology has become a widely adopted alternative because it offers flexibility, scalability, and ease of data management. This study employs a qualitative approach using descriptive methods through a literature review. Data were obtained from various scientific journals, books, conference proceedings, and other references discussing multimedia databases, cloud computing, network latency, and the cost efficiency of cloud services. The results of the study indicate that the implementation of cloud-based multimedia databases can enhance storage flexibility, accelerate data access processes, and reduce operational costs compared to conventional storage systems. On the other hand, the implementation of this technology still faces several challenges, such as high latency under certain network conditions, data security, and dependence on cloud service providers. Overall, the design of a cloud-based multimedia database is an effective solution for supporting faster, more efficient digital data management that meets the needs of today’s evolving information technology landscape.